Lysosome (Dys)function in Atherosclerosis—A Big Weight on the Shoulders of a Small Organelle - Marques, André R. A.; Ramos, Cristiano; Machado-Oliveira, Gisela; Vieira, Otília V. (Frontiers in Cell and Developmental Biology, 2021)
Atherosclerosis is a progressive insidious chronic disease that underlies most of the cardiovascular pathologies, including myocardial infarction and ischemic stroke. The malfunctioning of the lysosomal compartment has a central role in the etiology and pathogenesis of atherosclerosis. Lysosomes are the degradative organelles of mammalian cells and process endogenous and exogenous substrates in a very efficient manner. Lysosomal dysfunction and consequent inefficient degradation of modified low-density lipoproteins (LDL) and apoptotic cells in atherosclerotic lesions have, therefore, numerous deleterious consequences for cellular homeostasis and disease progression. Lysosome dysfunction has been mostly studied in the context of the inherited lysosomal storage disorders (LSDs). However, over the last years, it has become increasingly evident that the consequences of lysosomal dysfunction are more far-reaching, also influencing the progression of multiple acquired human pathologies, such as neurodegenerative diseases, cancer, and cardiovascular diseases (CVDs). During the formation of atherosclerotic plaques, the lysosomal compartment of the various cells constituting the arterial wall is under severe stress, due to the tremendous amounts of lipoproteins being processed by these cells. The uncontrolled uptake of modified lipoproteins by arterial phagocytic cells, namely macrophages and vascular smooth muscle cells (VSMCs), is the initial step that triggers the pathogenic cascade culminating in the formation of atheroma. These cells become pathogenic “foam cells”, which are characterized by dysfunctional lipid-laden lysosomes. Here, we summarize the current knowledge regarding the origin and impact of the malfunctioning of the lysosomal compartment in plaque cells. We will further analyze how the field of LSD research may contribute with some insights to the study of CVDs, particularly how therapeutic approaches that target the lysosomes in LSDs might could be applied to hamper atherosclerosis progression and associated mortality.